(untitled) (PerCursos, 2024)
In Brazil, the black population represents one of the groups most affected by socioeconomic vulnerability and by various forms of violence perpetrated institutionally and culturally, many of which with the collusion of the State. Part of this context, the educational exclusion and educational inclusion-exclusion that affects millions of black brazilians are processes that need to be better understood and combated. In this article, understand that black intellectuals can contribute in so many different ways. The analytical approach that is privileged focuses on problematizing the possible causes and causes of the absence/presence of productions by black intellectuals such as Sueli Carneiro, Lélia Gonzalez, bell hooks, Conceição Evaristo, Nilma Lino Gomes, Chimamanda Adichie, among many others, in the curriculum of undergraduate and postgraduate disciplines at Brazilian universities. This study is described by its theoretical foundation mainly in black feminist epistemology, tends to use, as part of the methodological design, ethnographic strategies (participant observation and recording of narratives or products produced by students in the classroom context), in addition to bibliographical research. It was possible to verify the importance of the university assuming, in the present and in the future, an active role in combating the mechanisms that, within itself and in broader society, delegitimize black people as subjects of knowledge